HERBICIDAL EFFICACY OF ACETIC ACID AND CITRIC ACID BASE ON BROAD LEAF WEEDS OF MEDICINAL CROPS FIELDS - sri rahayuningsih; supriadi supriadi (Buletin Penelitian Tanaman Rempah dan Obat, 2014)
The study aims to determine the effectiveness of acetic acid based formula on broad leaf weeds grown in medicinal crop fields. Two experiments were conducted, i.e. on small plots (2 m x 3 m) of a farmer’s field in Ciapus, Bogor and on a larger plot (2 m x 8 m) at the Cicurug Experimental Station, Sukabumi. The formula consisted of a mixture of acetic acid + NaCl (AG) and acetic acid + citric acid (AC), and formulas of VAC, VACG which were enriched with wood vinegar (V). As control was a commercial synthetic herbicide 2,4 D amine. The acetic acid base formulas applied at two concentrations 10 and 15%, while 2,4-diamine was followed the recommendation (0.3%) using a knapsack sprayer with a flat-fan nozzle tip. Weed vegetations were observed visually before and at 2, 4, 6, and 8 weeks after treatments. Weed severity was recorded using a 0-4 scales (0 = 0-5% mortality ; 1 = 20-50% weeds died ; 3 = 50-75% eradicated and 4 = 75-100% weed were eradicated), as well as re-growth and dry weight of the weeds. The first and second experiment showed that AC, AG, VAC and VACG applied at 10 and 15% were effective in controlling broadleaf weeds. Mechanism of action the formula is a contact poison. Its effectiveness is equivalent to 2,4-D amine treatment dose of 1.5 l ha-1. Repeated application is necessary to prolong the effect of herbicide.